Its Great! Oops, No It Isnt - Gauch, Ronald (Springer, 2017)
The truth is, few people know the first thing about clinical research. The public reads about a medical research project that announces unbelievable results for a miraculous drug. Some years later, another investigation completely wipes out those initial favorable findings. Hormones Cut Women’s Risk of Heart Disease (San Francisco Chronicle, 1994) Hormones Don’t Protect Women from Heart Disease, Study Says (Washington Post, 2001) The people are confused because we do not understand the process behind these conflicting results. Our health, and in fact, our very lives are dependent on clinical trials, but we know little about them. This book explains the issues the public needs to be aware of when it comes to clinical research. It uncovers the problems in medical investigations that can not be overcome no matter how much care and diligence medical researchers bring to a research project. The basic premise that drives the writing is that it is impossible for medical researchers to guarantee that they can get all the right answers from a single study. No matter how good the investigators are, no matter how well a study is planned, no matter how carefully the plans are executed and no matter how conscientiously the results are analyzed and interpreted – the answer may still be wrong. The deck is stacked against medical researchers and the public – you – should be skeptical of the results no matter how impressive they seem on the surface.